All-polymer based polymorph skin with controllable surface texture. (21st May 2019) - Bolson, Natanael; Singh, Devendra; Lube, Vinicius; Lubineau, Gilles
Abstract: Smart skins are integrating an increasing number of functionalities to improve the interactions between the equipped systems (robots or artificial systems) and their ambient environment. Here, we introduce a controllable texture as a new functionality, based on an innovative soft technology that leverages the strong electro-mechanical coupling of our all-polymer design, which can be easily embedded to a wide range of systems. The device comprises a polymer-based heating element [doped PEDOT:PSS (poly-(3, 4 ethylenedioxythiophene): poly (styrene sulfonic acid))], a polymer-based soft actuator (Ecoflex 00–50/ethanol) and a polymer-based casing [PDMS (polydimethylsiloxane)]. We introduce a smart pipe prototype module and use our controllable polymorph skin to tailor the interaction between the pipe and the fluid. This allows us to obtain a 50% reduction of the friction coefficient in turbulent regime, between non-actuated and actuated configurations. This concept may find applications in engineering fields such as smart skin-based touch control and controllable friction coefficients.